2008
DOI: 10.1002/cbf.1497
|View full text |Cite
|
Sign up to set email alerts
|

Production of cachexia mediators by Walker 256 cells from ascitic tumors

Abstract: In neoplasic cachexia, chemical mediators seem to act as initiators or perpetuators of this process. Walker 256 cells, whose metabolic properties have so far been little studied with respect to cancer cachexia, are used as a model for the study of this syndrome. The main objective of this research was to pinpoint the substances secreted by these cells that may contribute to the progression of the cachectic state. Since inflammatory mediators seem to be involved in the manifestation of this syndrome, the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
1
16
0
3
Order By: Relevance
“…Our findings are surprising given the strong association between the acute phase response and reduced hepatic fatty acid oxidation. 60 Although it is possible that the acute phase response was not as robust in our study of early cachexia, differences in cytokine production (thus, the acute phase response) between the colon-26 and Walker 256 cachexia models 61,62 may better explain these disparate findings. In summary, in the present study we found PKA-induced lipolysis is enhanced in early cancer cachexia which coincided with elevated total energy expenditure and increased expression of markers of BAT thermogenesis when food intake is considered and the hepatic acute phase response.…”
Section: Discussionmentioning
confidence: 83%
“…Our findings are surprising given the strong association between the acute phase response and reduced hepatic fatty acid oxidation. 60 Although it is possible that the acute phase response was not as robust in our study of early cachexia, differences in cytokine production (thus, the acute phase response) between the colon-26 and Walker 256 cachexia models 61,62 may better explain these disparate findings. In summary, in the present study we found PKA-induced lipolysis is enhanced in early cancer cachexia which coincided with elevated total energy expenditure and increased expression of markers of BAT thermogenesis when food intake is considered and the hepatic acute phase response.…”
Section: Discussionmentioning
confidence: 83%
“…After 7 days of growth, the ascitic tumour was harvested from the peritoneal cavity and suspended in PBS, pH 7.4. The cells were separated from the ascitic fluid by centrifugation at 570 × g for 15 min at 4 • C; the cell pellet (tumour cells plus erythrocytes) was then washed once with the same PBS solution [22]. The volume of cell suspensions was adjusted to 500 L and cell viability was evaluated by the Trypan Blue exclusion test, considering only tumour cells presenting on the Neubauer chamber.…”
Section: Animals and Tumour Implantationmentioning
confidence: 99%
“…[9] These pro-inflammatory circulating factors are known to play a key role in the onset of cachexia-related inflammation [9,10] and to contribute to and trigger both increased muscle breakdown and decreased muscle protein synthesis in CACS patients. [11][12][13][14][15][16] IL-1b, IL-6, and TNFa are produced by tumor cells both in animal models of cachexia [17] and in cancer patients with CACS. [18] In cancer patients, the production of pro-inflammatory cytokines -an expression of systemic inflammation -may lead to an acute-phase response [19] characterized by an increase in acute-phase proteins [20] and by decreased synthesis of albumin, pre-albumin, and transferrin.…”
Section: Introductionmentioning
confidence: 99%